A finite element technique and results of continual fracture process modeling - Bazhenov, V.; Pyskunov, S. (KNUCA, 2014)
The techniques of modeling of continual fracture process for space circular and prismatic bodies under long-term static or cyclic force loading condition and some results of determination of responsible parts lifetime is presented in this paper. The scalar damage parameter is used to describe the material continual fracture process. A stress-strain problem solution made with semianalytic finite element method (SFEM). It‘s shown , that the value of residual lifetime could be differ significantly for different loading condition and object configuration.
Конечноэлементная методика и результаты моделирования процессов континуального разрушения
Keywords: long-term loading condition; creep; damage; continual fracture; lifetime; spatial problem; semianalytic finite element method (SFEM); длительное нагружение; ползучесть; повреждаемость; континуальное разрушение; ресурс; пространственная задача; полуаналитический метод конечных элементов (ПМКЭ)